An Unusual Pulmonary Condition Presenting following Trauma - John RA Turkington; Eamon McAteer; Rory P Convery (Canadian Respiratory Journal)
An 18-year-old man presented to the emergency department following an assault. He complained of left-sided pleuritic chest pain and difficulty breathing. Clinical examination revealed reduced air entry and coarse crepitations at the left lung base. A chest x-ray showed a large opacity at the left lung base that contained multiple cystic areas with air-fluid levels. Due to the history of trauma, a provisional diagnosis of a ruptured hemidiaphragm with small bowel herniation was made. Further imaging, including ultrasound, spiral computed tomography and magnetic resonance angiography, showed an aberrant vessel supplying the opacity and drainage into the pulmonary venous system. A diagnosis of a bronchopulmonary sequestration (intralobar type) was made. The differential diagnosis of the radiographic appearance is also discussed.